Краткий словарь иностранных слов - Локшина Слава Мироновна (Русский язык, 1984)
Экземпляры: КХ (20230927) / Инвентарный номер: 829783 / Сис.шифр: 4Р(03) / Авт.знак: Л 73 / ГРНТИ: 16 / ББК: 81.411.2-42